Study Determinants of Labor Absorption in Layer Breeder Chicken Farming Sector Businesses - Himawan Sutanto; Ida Ayu Putri Suprapti; Iwan Harsono; Irwandi (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2024)
This research aims to determine the determinant factors for employment in the laying hen farming sector. In this research, the independent variable is used where (wages X1, productivity X2 and capital X3) and the dependent variable is (labor absorption Y). The aim of this research is to find out whether wages, productivity and capital influence labor absorption in egg-laying chicken farming businesses in Sidrap Regency, which is known as one of the largest egg-laying chicken producing districts in South Sulawesi. The method used is quantitative descriptive. The sample in this research consisted of 85 egg-laying chicken farming business units in Sidrap Regency. Sampling was carried out by taking the entire population considering that the population was less than 100 units. Research data was obtained by distributing questionnaires to 85 respondents. Data analysis was carried out using multiple linear regression. Based on the results of the analysis carried out, it can be seen that wages and capital have a positive effect on labor absorption, while productivity has no effect on labor absorption in egg-laying chicken farming businesses in Sidrap Regency.